Invasive Mole With Impending Uterine Rupture : A Case Report - Syamel Muhammad (Journal of Midwifery, 2022)
Gestational  Trophoblastic  Disease  (GTD)  is an abnormal placenta, composed of a spectrum of premalignant to malignant disorders. In Indonesia, GTD incidence is particularly challenging to estimate, since not all cases will be reported or recognized. It classified into hydatidose mole and gestational trophoblastic neoplasia (GTN). One of those clinicopathological classification of GTN is malignant invasive mole. It is likely to be the cause of increased maternal mortality in Indonesia if the disease is not well diagnosed and treated.We reported the case, a 28 years old woman who had a invasive mole with impending uterine rupture. She had a pervaginam bleeding symptoms since 3 weeks after post curetase due to hydatidose mole indication. She also had multiple abortus history.